Role of asphaltene in changing wettability of reservoir rocks - Yunan, Mat Hussin; Idris, Ahmad Kamal (1995)
This paper reports an investigation on the precipitation and adsorption of asphaltene on reservoir rocks and other mineral. This paper also discussed the effect of asphaltene adsorption on water-oil distribution and oil transport. Results shows that asphaltene play a major role in controlling wettability of reservoir rocks. The detail experimental work and results are available in full text article.